Pemberian Stimulasi Sensori Auditorius terhadap Perubahan Nilai Glasgow Coma Scale (GCS) pada Pasien Penurunan Kesadaran - Henni Febriawati; Juli Andri; Yosi Losyanti; Padila Padila (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the effectiveness of giving auditory sensory stimulation to changes in the Glasgow coma scale (GCS) value in patients with impaired consciousness. The research design used was a quasi-experimental group pre-test and post-test design. The results of the univariate analysis found that before the auditory sensory stimulation intervention was given, the majority of 12 respondents (40%) were at the level of stupor awareness. After the intervention, most respondents, eight people (26.7%), were at the somnolence level of understanding. The bivariate analysis results showed that the p-value for intervention was (0.002). In conclusion, there is an effect of auditory sensory stimulation on changes in the GCS value of patients with decreased consciousness. Keywords: Glasgow Coma Scale (GCS), Auditory Sensory Stimulation